2016
DOI: 10.2147/jpr.s105506
|View full text |Cite
|
Sign up to set email alerts
|

Transsacrococcygeal approach to ganglion impar: radiofrequency application for the treatment of chronic intractable coccydynia

Abstract: ObjectiveCoccydynia is defined as pain in the coccygeal region. Among the many causes of coccydynia, the most common cause is trauma as a result of falling on the buttocks, repetitive microtrauma, or childbirth. Several methods are currently used for the treatment of coccydynia, including nonsteroidal anti-inflammatory drugs, intrarectal manipulation, epidural injections, ganglion impar blocks, and radiofrequency treatment (RFT). Wemm and Saberski used the transacrococcygeal methods to reduce tissue trauma. RF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 13 publications
1
27
0
17
Order By: Relevance
“…The examinations carried out in the sixth month of the treatment showed that 37 patients had a successful outcome, whereas treatment failed in four of the patients. 93 …”
Section: Ganglion Impar Block (Gib)mentioning
confidence: 99%
“…The examinations carried out in the sixth month of the treatment showed that 37 patients had a successful outcome, whereas treatment failed in four of the patients. 93 …”
Section: Ganglion Impar Block (Gib)mentioning
confidence: 99%
“…Injections around the coccyx, usually at the sacrococcygeal junction or around the sacrococcygeal ligaments, of local anesthetic with steroid can be both diagnostic and therapeutic [ 9 ]. Another approach is to target the ganglion impar, also known as the ganglion of Walther [ 10 ]. The ganglion impar is the pelvic portion of the sympathetic trunk located in the midline anterior to the sacrococcygeal junction.…”
Section: Discussionmentioning
confidence: 99%
“…Dolecek et al 4 described 18 patients treated with RF reported a satisfactory pain relief in 57% of patients at 12 months follow up while Demircay et al 8 reported a good pain relief lasting for 6 months in 90% of 10 patients treated with RF. Adas et al 9 described 41 patients treated with RF for coccydynia and reported a successful outcome at 6 months follow up in 90.2% of patients. 9 Even if only few studies investigated RF ablation, this technique seems to provide comparable results as chemical neurolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Adas et al 9 described 41 patients treated with RF for coccydynia and reported a successful outcome at 6 months follow up in 90.2% of patients. 9 Even if only few studies investigated RF ablation, this technique seems to provide comparable results as chemical neurolysis. The small number of studies and population studied prevents from getting precise data regarding the magnitude and frequency of adverse events with both RF and neurolysis which appears to be relatively safe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation